PERILAKU IMPULSIVE BUYING MASYARAKAT BANDUNG RAYA PADA MASA PANDEMI COVID-19 BERDASARKAN PERBEDAAN GENDER: Evaluasi Program A-Life - Ravenska, Nanda; Zulvia, Pepi (LP2M Institut Teknologi dan Bisnis Asia Malang, 2022)
This study was conducted to understand impulsive buying behaviour based on gender (male and female) during the pandemic. The study used a survey in the Greater Bandung area (Bandung City, Cimahiy City, Bandung Regency and West Bandung Regency) using quantitative methods and analysis of different tests. Judging from the overall results in the Levene's Test difference test, it proved that impulsive buying answered the hypothesis that assuming (equal variances assumed) there was no significant difference (0.606>0.005) between men and women in the pattern of impulsive buying behaviour during a pandemic. So the results of the study show that there is no difference between men and women in impulsive buying behaviour during the Covid-19 pandemic.